Tumor imaging and photothermal therapy in second near infrared window: A systematic review and meta-analysis - Fan, Fuhan; Hou, Ya; Zhang, Yating; Zeng, Yong; Zhang, Yi; Zhang, Sanyin; Meng, Xianli; Wang, Xiaobo (Frontiers in Oncology, 2022)
Background: Second near-infrared window (NIR-Ⅱ, 1000-1700 nm) technology for tumor imaging and photothermal therapy (PTT) is an innovative method for tumor diagnosis and treatment. The NIR-Ⅱ probe can specifically identify tumor cells, and effectively convert light energy into heat energy under the irradiation of NIR laser, thus achieving the integration of non-invasive tumor diagnosis and treatment. In the present study, we conducted a systematic review and meta-analysis of preclinical investigations to corroborate the efficacy and safety of photothermal therapy. Methods: Relevant preclinical data were retrieved by searching PubMed, Web of Science, CNKI, WANFANG and VIP information databases. And the acquired data were analyzed by RevMan Version 5.3 software. Results: According to the inclusion criteria, forty-two articles relating to NIR-Ⅱ tumor imaging and PTT were recruited for further in-depth analysis. The NIR-Ⅱ photoacoustic and fluorescence imaging could quickly and accurately identify tumor in mice, manifesting higher signal intensity on tumor site than that of normal tissue. After PTT, the tumor volume of mice decreased miraculously [RR=8.49, 95%CI (4.64, 15.55), P<0.00001], and even disappeared completely [RR=7.01, 95%CI (3.04, 16.13), P<0.00001] with no potential risk of affecting the blood routine. Conclusions: PTT guided by NIR-Ⅱ imaging can effectively diagnose the tumor lesion and eliminate it with the advantages of non-invasive and higher biosafety.